(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Organizations all over the globe create a significant quantity of data on a daily basis, owing to the introduction of the World Wide Web and the advent of ecommerce apps and social networking sites. The most fundamental challenge both organizations and users face while ensuring secure data transfer over the internet is information security. As a society the more we are progressing towards an era of digital information, the more issues concerning network security are arising. While the number of people accessing the internet is increasing, cyber-attacks on the other hand are becoming increasingly common. It is necessary to safeguard computer and network security, which are both significant problems. The system is hampered by the parasitic hubs. It may make use of the assets of other hubs while still protecting its own. In this article, we have provided a brief introduction of network security and the different approaches that may be used to improve network security, such as cryptography